Morphology and Molecular Characterization of Four Types of Ramies (Boehmeria nivea (L.) Gaud) Collection Experimental Farm Faculty of Agriculture Andalas University - Yulfa, Denny; Mayerni, Reni; Yusniwati, Yusniwati (International Journal of Environment, Agriculture and Biotechnology, 2019)
The purpose of this study was to collect and determine the morphological and molecular character of the ramies in West Sumatra. This study was conducted in May-October 2018 Experimental Farm, Faculty of Agriculture, University of Andalas Padang. This activity also used the clone Padang 3 and Ramindo 1 as a comparison. The results of this study indicated that the ramie plant could grow to a height of 1058 meters above sea level to the point where the coordinates 0 ° 15'30 "South Latitude and 100 ° 15'45" east longitude. Ramie highest Situjuah accession 150.03 cm and the lowest at 91.7 cm Matur accession. The longest and widest leaf observations contained in the accession Situjuah while the shortest and smallest obtained at Matur accession. On accession Situjuah, Matur, and clones Ramindo 1 had male and female flowers but clone Padang 3 only had female flowers. Harvesting fastest in clones Ramindo 1 was 123 days and the longest in clones Padang 3 was 133 days. The numbers of banding pattern resulting from PCR amplification were 74 tapes (68 a polymorphic bands while the rest was the number of monomorphic bands)